2014
DOI: 10.1016/j.sjbs.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Trigonella foenum-graecum on thioacetamide induced hepatotoxicity in rats

Abstract: Trigonella foenum-graecum belongs to the family Fabaceae and is indigenous to countries that lie on the eastern shores of the Mediterranean Sea and is also cultivated in India, Egypt and Africa. This study provides the evidence indicating the therapeutic effect of the extract prepared from the dried seeds of Trigonella foenum-graecum on an animal model of hepatotoxicity and on cell proliferation. Rats were induced liver cirrhosis by thioacetamide (0.03% in water for 16 weeks). Transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…In the present study, it was revealed that the oral administration of NaNO 2 for 15 days induced neuronal damage in the mice brain, as indicated by histopathological examination compared to the control group. Our findings are consistent with the earlier studies carried out to determine the negative effects of NaNO 2 on cell membrane by inhibiting membrane bound enzymes in rat brain [14]. Current findings suggest that T. foenum graecum extracts can inhibit the neurodegeneration in brain hippocampus and cortex.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was revealed that the oral administration of NaNO 2 for 15 days induced neuronal damage in the mice brain, as indicated by histopathological examination compared to the control group. Our findings are consistent with the earlier studies carried out to determine the negative effects of NaNO 2 on cell membrane by inhibiting membrane bound enzymes in rat brain [14]. Current findings suggest that T. foenum graecum extracts can inhibit the neurodegeneration in brain hippocampus and cortex.…”
Section: Discussionsupporting
confidence: 92%
“…The present outcomes demonstrate a significant increase in AST, ALT and ALP because of aflatoxin infusion. Rise of liver catalysts was as per that revealed by many examinations (Salama et al, 2013;Zargar, 2014 andKim et al, 2014). Sherif et al, (2009) indicated that liver enzymes increased after liver damage because of increased membrane permeability or because of liver cell necrosis and cytosol leakage into the serum.…”
Section: Discussionmentioning
confidence: 54%
“…Clinical trials were included if they had evaluated the healing of venous ulcers with the topical use of herbal medicines. Studies that evaluated ulcer healing with the use of herbal medicines in animals , ulcers with other etiologies , cost‐benefit and reporting cases were excluded .…”
Section: Methodsmentioning
confidence: 99%